The average rate of change of f(x) on the interval [a,b] is f(b)−f(a)b−a.
We have that a=1254, b=6103100, f(x)=20(54)x.
Thus, f(b)−f(a)b−a=20(54)(6103100)−(20(54)(1254))6103100−(1254)=−58207660913467407226562517167001203595951472642–√5–√4+542101086242752217003726400434970855712890625197922048572373973475376871275743307366424750⋅53100.
Answer: the average rate of change is −58207660913467407226562517167001203595951472642–√5–√4+542101086242752217003726400434970855712890625197922048572373973475376871275743307366424750⋅53100≈550754.870532511
pls put as brainliest
We have
1G = 12.05 - 3D;
Then,
2D + 3( 12.05 - 3D) = 15.50;
2D + 36.15 - 9D = 15.50;
- 7D = - 20.65;
D = 2.95;
Finally, G = 12.05 - 3 x 2.95;
G = 3.20;
Answer:
it's A. sorry for the late answer